2022
DOI: 10.3389/fsurg.2022.989513
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and research hotspots in the field of full endoscopic spine surgery: A bibliometric analysis

Abstract: PurposeWe aimed to comprehensively analyze the current status, hotspots, and trends in full endoscopic spine surgery (FESS) research using bibliometric analysis and knowledge domain mapping.MethodsThe Web of Science database was used to screen FESS-related articles published between January 1, 1993 and June 10, 2022. The evaluation involved the following criteria: total number of articles; H-index; and contributions from countries/regions, institutions, journals, and authors.ResultsA total of 1,064 articles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…A bibliometric analysis highlighted that the vast majority of research into endoscopic spine techniques (over 50%) of these are published in and originated in China and South Korea. 7 The regions identified that demonstrated larger interest and publications within the field of endoscopic spine techniques also had noticeably higher rates of native surgeon training in ESS, as they go on to utilise and implement this in practice. 8 There were statistically significant differences in spinal endoscopy between Asian vs. non-Asian surgeons, further highlighting the willingness to learn and implement more progressive techniques.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A bibliometric analysis highlighted that the vast majority of research into endoscopic spine techniques (over 50%) of these are published in and originated in China and South Korea. 7 The regions identified that demonstrated larger interest and publications within the field of endoscopic spine techniques also had noticeably higher rates of native surgeon training in ESS, as they go on to utilise and implement this in practice. 8 There were statistically significant differences in spinal endoscopy between Asian vs. non-Asian surgeons, further highlighting the willingness to learn and implement more progressive techniques.…”
Section: Discussionmentioning
confidence: 98%
“…Research and early technique implementation are particularly concentrated within a small group of countries and authors. A bibliometric analysis highlighted that the vast majority of research into endoscopic spine techniques (over 50%) of these are published in and originated in China and South Korea [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A témakörben 1993-tól 2022-ig több mint 1500 tanulmányt publikáltak, melyek több mint 65%-a ázsiai országból származik (37,8% Kína, 24% Dél-Korea, 5% Japán), ezt követi az Egyesült Államok (16,1%), majd Németország (5,1%) [42]. Az országok, illetve régiók közötti tudományos teljesítménybeli különbségek többtényezősök, és főként a társadalmi-gazdasági szempontok, az általános kutatási kapacitás, a tudományos kutatásra fordított nemzeti kiadások és a népességszámbeli különbségek okozzák [43,44].…”
Section: Endoszkópos Gerincműtétekunclassified